Strategic Interests of Germany in the Balkans at the Turn of 20-21 Centuries - A. Latkov (Vestnik MGIMO-Universiteta, 2014)
After the reunification of Germany and the transition of some countries of central and Eastern Europe under the control of the West, radical changes in the European political system have occurred. Germany turned into a powerful state and began to provide the strategy for independent foreign policy, in which the regional policy in the Balkans, Caucasus and Middle East took the significant place. Germany tried to expand its influence to the countries of Balkan Peninsula, in alliance with Austria-Hungary against Russia, as well as in the beginning of 21st century. However, in the end of 20th century, after several failures in the foreign policy, Germany turned to Russia. Despite its expansionist policy, Germany had to coordinate every step with international organizations or even transfer them issues of conflict resolution in the region. Constantly competing with its allies (mainly the U.S. and UK), Germany was trying to build its foreign policy strategy in the way of increasing its influence in the strategically important region.